Slow-release material with antibacterial property and preparation method thereof
By modifying ZIF-8 with Co2+ and Ni2+, compounding with sodium alginate, loading tetracycline, forming a sustained-release material with antibacterial properties, solving the problems of poor antibacterial properties and poor sustained-release properties of existing antibacterial materials, achieving efficient and stable antibacterial effects and long-term sustained-release properties.
Patent Information
- Application Number
- CN202411682404.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-04
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing antibacterial materials are not antibacterial and lack sustained release capabilities. They require frequent administration to maintain efficacy, affecting patient convenience and may have side effects on normal cells.
By introducing Co2+ and Ni2+ modification to ZIF-8, and compounding with sodium alginate, loading tetracycline to form a sustained-release material with antibacterial properties. This material achieves stable drug release through the pore structure of ZIF-8, enhances antibacterial effects and improves biocompatibility.
It significantly improves the ability of the material to inhibit bacteria, achieves long-term sustained release of drugs, reduces the phenomenon of excessively rapid drug release, improves biocompatibility and stability, and is suitable for large-scale production.
Smart Images

Figure CN119548646A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal organic framework materials, in particular to a sustained-release material with antibacterial properties and a preparation method thereof. Background Art
[0002] Metal-organic framework materials (MOFs) have important application potential in the fields of drug carriers and antibacterial materials due to their high specific surface area, adjustable pore structure and good biocompatibility. With the increase of bacterial resistance, the bactericidal effect of traditional antibacterial materials has gradually decreased, and they usually lack sustained-release ability, requiring frequent administration to maintain efficacy, which not only causes inconvenience to patients, but may also affect normal cells. Therefore, the development of new materials with both antibacterial and sustained-release properties has become a research hotspot. ZIF-8, as a classic MOFs material, has excellent chemical stability and biocompatibility and is an ideal basic material for drug carriers. However, the antibacterial and sustained-release properties of ZIF-8 still have certain limitations in certain application scenarios; for this reason, we propose a sustained-release material with antibacterial properties and a preparation method. Summary of the invention
[0003] The purpose of the present invention is to provide a sustained-release material with antibacterial properties and a preparation method thereof, which has excellent antibacterial effect and stable sustained-release performance, and solves the problems of weak antibacterial properties and uneven drug release of existing materials.
[0004] To achieve the above object, the present invention provides the following technical solution: a sustained-release material with antibacterial properties, the sustained-release material consisting of the following components:
[0005] Core component group: ZIF-8; Modified component group: Co 2+ 、Ni 2+ ; Composite component group: sodium alginate; Loading component group: tetracycline; The ZIF-8 is composed of Zn 2+ (zinc nitrate hexahydrate), 2-methylimidazole.
[0006] Preferably, the ratio of each component is in the range of:
[0007] Core component group: ZIF-8, Zn 2+ (zinc nitrate hexahydrate) is 0.8-1.0g; 2-methylimidazole is 0.4-0.6g; Modified component group: Co 2+ 0.1-0.2g; Ni 2+ It is 0.05-0.15g; complex component group: sodium alginate is 1-1.5g; loading component group: tetracycline is 0.1-0.15g.
[0008] Preferably, the specific ratio range of each component is:
[0009] Core component group: ZIF-8, Zn 2+ The ratio range is 0.85-0.95g; the ratio range of 2-methylimidazole is 0.45-0.55g; the modified component group: Co 2+ The ratio range is 0.12-0.18g; Ni 2+ The ratio range of the composite component group: sodium alginate is 1.1-1.3g; the loading component group: tetracycline ratio range is 0.11-0.14g.
[0010] Preferably, the specific surface area of ZIF-8 is in the range of 1100-1300 m 2 / g, its pore size range is 1.2-1.5nm, and its solubility in water is less than 0.01g / L; the Co 2+ The surface cobalt ion ratio of the modified ZIF-8 is in the range of 10-12%, and the antibacterial rate against Escherichia coli is in the range of 85-98%. 2+ The nickel ion attachment rate of the modified ZIF-8 is in the range of 8-10%, and the stability time in the solution is in the range of 24-30 hours; the drug loading efficiency of the tetracycline in ZIF-8 is in the range of 70-80%, and the cumulative release amount thereof within 6-8 hours at 37°C is in the range of 60-80%.
[0011] A method for preparing a sustained-release material with antibacterial properties comprises the following steps:
[0012] S1. Synthesis of ZIF-8 framework material:
[0013] S11, preparation of mixed solution: 0.8-1.0g of zinc nitrate hexahydrate and 0.4-0.6g of 2-methylimidazole were dissolved in 80mL of NN-dimethylformamide (DMF), the stirring speed was 300rpm, the stirring time was 15 minutes, and the temperature was controlled at 25°C; S12, hydrothermal reaction: the mixed solution obtained in S11 was transferred to an autoclave, the temperature was increased to 140°C at a heating rate of 5°C / min, and crystallized at this temperature for 24 hours; S13, separation and drying of solid powder: the product after the reaction was completed was centrifuged, washed 3 times with 50mL of DMF and methanol respectively, and then dried at 80°C overnight to obtain ZIF-8 skeleton powder;
[0014] S2. Modification and compounding of ZIF-8:
[0015] S21, Co 2+ Modification: 0.1-0.2 g of cobalt sulfate hexahydrate was dissolved in 20 mL of deionized water, and then 0.5 g of ZIF-8 skeleton powder was added, and the stirring speed was 300 rpm for 1 hour to complete the modification of surface cobalt ions; S22, Ni2+ Modification: 0.05-0.15 g of nickel chloride was dissolved in 20 mL of deionized water and added to the ZIF-8 / Co obtained in S21. 2+ The composite was stirred at a speed of 300 rpm for 1 hour to complete the modification of nickel ions; S23, solid separation and drying: the modified product was centrifuged, washed with deionized water for 3 times, and dried at 60 ° C for 12 hours to obtain Co 2+ and Ni 2+ Modified ZIF-8;
[0016] S3. Preparation of sodium alginate complex:
[0017] S31, preparation of sodium alginate solution: at room temperature, dissolve 1.0-1.5 g of sodium alginate in 100 mL of deionized water, stirring at a speed of not less than 350 rpm, stirring until completely dissolved to form a sodium alginate solution; S32, formation of composite material: gradually add 0.8-1.0 g of modified ZIF-8 to the sodium alginate solution of S31, stirring at a speed of 300 rpm, stirring for 20 minutes, to form a sodium alginate / ZIF-8 composite;
[0018] S4. Loading and drying of tetracycline:
[0019] S41, preparation of tetracycline solution: dissolve 0.1-0.15 g of tetracycline in 30 mL of PBS solution with a pH of 7.4, with a stirring speed of 400 rpm and a stirring time of 15 minutes; S42, impregnation and loading of tetracycline: add 0.5 g of the composite material obtained in S32 to the tetracycline solution of S41, and stir at room temperature for 24 hours to fully load the tetracycline; S43, separation and freeze-drying of the solid: centrifuge the impregnated product, discard the supernatant, wash 3 times, and freeze-dry the solid for 12 hours to obtain the final sustained-release material.
[0020] Preferably, in step S11, the pH of the mixed solution of zinc nitrate hexahydrate and 2-methylimidazole is adjusted to maintain the pH value in the range of 6.5-7.0; in the hydrothermal reaction process of step S12, an intermittent heating method is also adopted, that is, the temperature is raised from 100°C to 140°C every 30 minutes and maintained at the highest temperature for 30 minutes; in the drying process of step S13, constant temperature air drying is adopted, the temperature range is controlled at 60-70°C, and the drying time is 12-16 hours.
[0021] Preferably, in steps S21 and S22, Co 2+ and Ni 2+The modification process also includes adding sodium citrate as a chelating agent, and the addition ratio is 0.05-0.1% of the total mass of the solution; in the drying process of step S23, vacuum drying is adopted, the vacuum degree is not less than 0.08MPa, and the drying time ranges from 8 to 10 hours; in the centrifugal separation process of step S23, the centrifugal speed is 4000-5000rpm, and the centrifugal time is 10 to 15 minutes.
[0022] Preferably, in the sodium alginate solution preparation process of step S31, the solution stirring speed is gradually increased to 400 rpm, and the dissolution environment is maintained within a temperature range of 30-35°C; in the tetracycline immersion loading process of step S42, ultrasonic assisted loading is also included, the ultrasonic frequency range is 20-40kHz, and the ultrasonic time is 15-20 minutes; in the freeze-drying process of step S43, the sample is pre-cooled to -20°C and then vacuum freeze-dried for 10-12 hours.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. This paper introduces Co 2+ and Ni 2+ The modification of ZIF-8 improves the material's ability to inhibit bacteria, and the antibacterial effect is significantly enhanced;
[0025] 2. The composite of sodium alginate and ZIF-8 improves the biocompatibility of the material and enhances the sustained release performance of the drug;
[0026] 3. By rationally designing the pore structure of ZIF-8, the stable release of the drug was achieved, avoiding the phenomenon of excessive initial release;
[0027] 4. The preparation process of the present invention is simple and easy, suitable for large-scale production, and the prepared material has good stability and practicality. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is the standard curve diagram of tetracycline of the present invention;
[0029] Figure 2 is a scanning electron microscope image of the sample;
[0030] Figure 3 It is a bar graph of the MTT test results of the present invention;
[0031] Figure 4 It is a line graph of the survival rate of phagocytes of the present invention;
[0032] Figure 5 It is a line graph of tetracycline drug loading rate of the present invention;
[0033] Figure 6 is a line graph of the release rate of tetracycline of the present invention;
[0034] Figure 7 is the release rate of tetracycline at different pH values of the present invention;
[0035] Figure 8 This is a schematic diagram of the structure of the antibacterial sustained-release material of the present invention;
[0036] Fig. 9 The figure is a schematic diagram of the steps of the method for preparing the antibacterial sustained-release material of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] See also Figures 1 to 9 The present invention relates to a sustained-release material with antibacterial properties, which is mainly composed of four major component groups: a core component group, a modified component group, a composite component group and a loading component group. This sustained-release material has excellent antibacterial properties and can also achieve slow release of drugs to improve the therapeutic effect. Each component group is explained in detail below.
[0039] 1. Core component group: ZIF-8: ZIF-8 is a metal organic framework material composed of Zn 2+ (zinc nitrate hexahydrate) and 2-methylimidazole. The structural characteristics of ZIF-8 are high porosity and specific surface area, making it an ideal drug carrier. In the present invention, ZIF-8, as the core component group of the sustained-release material, plays the following roles:
[0040] Stability: ZIF-8 has good chemical stability and can maintain its basic structure under different pH conditions. Under weakly acidic conditions, ZIF-8 will partially collapse, accelerating drug release; while under neutral or weakly alkaline conditions, the structure of ZIF-8 is relatively stable, thus ensuring the sustained release of the drug.
[0041] Drug loading capacity: The porous structure and large specific surface area of ZIF-8 enable it to effectively load drug molecules, improve drug loading efficiency, and also ensure uniform distribution of drugs.
[0042] In practical applications, the preparation of ZIF-8 includes a mixed reaction of metal zinc ions and organic ligands, and crystallization through a hydrothermal reaction, so that ZIF-8 forms a regular framework structure. This synthesis method not only ensures the physical and chemical properties of ZIF-8, but also provides a basis for subsequent modification and loading steps.
[0043] 2. Modification group: Co 2+ and Ni 2+ In the present invention, ZIF-8 is modified by Co 2+ and Ni 2+ Two metal ions, the addition of these two ions is to further enhance the antibacterial effect of the sustained-release material; Co 2+ Modification: Co modification on the surface of ZIF-8 2+ Can enhance its antibacterial properties. 2+ The distribution of Co in the metal organic framework enables ZIF-8 materials to have a strong inhibitory effect on a variety of bacteria (such as Escherichia coli and Staphylococcus aureus). 2+ The antibacterial rate of the modified ZIF-8 in the Escherichia coli antibacterial experiment can reach 85-90%, which shows its potential value in practical applications. 2+ Modification: Ni 2+ The introduction of Ni is mainly to further enhance the antibacterial activity and overall stability of the material. 2+ A more stable composite structure can be formed, which helps to prolong the duration of the antibacterial effect. 2+ and Ni 2+ It is gradually introduced through a solution impregnation method, which ensures the uniformity of modification and also helps to improve the antibacterial properties and sustained-release effect of the material.
[0044] 3. Composite component group: Sodium alginate. As a composite component group of the present invention, sodium alginate has good biocompatibility and sustained-release properties. After combining with ZIF-8, sodium alginate can form a composite hydrogel matrix, which plays a role in the following aspects: sustained-release performance: the composite of sodium alginate and ZIF-8 can effectively control the release rate of the drug, reduce the large-scale release of the drug in a short time, thereby achieving the purpose of prolonging the drug effect. Biocompatibility: Sodium alginate is a natural polysaccharide with good biocompatibility in the human body. As a composite material of ZIF-8, it can provide additional stability in drug carriers and reduce toxic reactions caused by too fast drug release. In the specific preparation process, sodium alginate is first dissolved in deionized water, and then reacts with ZIF-8 to form a uniform hydrogel structure.
[0045] 4. Loading component group: Tetracycline: Tetracycline is a broad-spectrum antibacterial drug, and is used as a loading component group of a sustained-release material in the present invention. By loading tetracycline into the pore structure of ZIF-8, the present invention can achieve the following effects: sustained-release effect: tetracycline can be released in a controlled manner in the carrier of ZIF-8, reducing local toxicity caused by rapid release and ensuring the persistence of drug efficacy. Experiments show that the drug loading efficiency of tetracycline in ZIF-8 can reach 70-80%, and at 37°C, its cumulative release in 6-8 hours reaches 60-80%. Antibacterial performance: After tetracycline is compounded with ZIF-8, it can directly inhibit bacterial cells, especially Escherichia coli and Staphylococcus aureus. In the specific loading process, tetracycline is introduced into the pores of ZIF-8 by solution impregnation to ensure uniform distribution of the drug and effective drug loading. This method not only improves the drug loading efficiency, but also ensures the sustained-release effect of the drug.
[0046] The antibacterial sustained-release material of the present invention not only clarifies the composition of the component groups, but also specifies in detail the ratio range of each component to ensure the best performance of the material. The following is a detailed description of the ratio range of each component group, explaining the role of each component within this range and its influence on the performance of the sustained-release material.
[0047] 1. Core component group: ZIF-8: ZIF-8 is the core component of this sustained-release material, and its ratio range is: Zn 2+ (zinc nitrate hexahydrate) is 0.8-1.0g; 2-methylimidazole is 0.4-0.6g; Zn 2+ (Zinc nitrate hexahydrate): As the main metal component of the ZIF-8 framework structure, Zn 2+ The stable formation of ZIF-8 framework can be ensured within the ratio range of 0.8-1.0g. 2+ When the amount is less than 0.8 g, the skeleton structure is incomplete, resulting in a decrease in the strength and drug loading capacity of the sustained-release material; 2+ When the amount exceeds 1.0 g, too much ZnO impurity may appear in the reaction product, affecting the antibacterial properties of the material.
[0048] 2-Methylimidazole: As an organic ligand of ZIF-8, 2-methylimidazole in the range of 0.4-0.6g is conducive to the orderly crystallization of ZIF-8. A ratio lower than 0.4g will lead to a decrease in the porosity of ZIF-8, thereby affecting the drug loading efficiency and sustained release performance; while a ratio exceeding 0.6g will increase the viscosity of the solution, affecting the efficiency of the reaction and the uniform formation of ZIF-8. At this ratio, ZIF-8 can maintain a high specific surface area and a good pore structure, laying a good foundation for subsequent modification and drug loading.
[0049] 2. Modification group: Co 2+and Ni 2+ , the ratio range of the modified component group is: Co 2+ 0.1-0.2g; Ni 2+ 0.05-0.15g; through Co 2+ and Ni 2+ The optimized ratio of ZIF-8 significantly improved the antibacterial properties and material stability. 2+ (0.1-0.2g): In this range, Co 2+ It can be evenly distributed on the surface of ZIF-8 and form a good combination with its skeleton structure, thus improving the antibacterial effect of the material. 2+ If the concentration of Co is less than 0.1 g, the modification effect is insufficient and it is difficult to achieve the expected antibacterial rate. 2 + If the amount exceeds 0.2 g, it may lead to excessive deposition of metal ions and affect the stability of the material.
[0050] Ni 2+ (0.05-0.15g):Ni 2+ The introduction of Ni is mainly to improve the antibacterial durability and stability of the material. The ratio range of 0.05-0.15g can ensure that Ni 2+ The uniform distribution of Ni and ZIF-8 forms a stable complex with the ZIF-8 framework, thereby further improving the antibacterial effect. 2+ If the concentration is less than 0.05 g, the desired modification effect cannot be achieved; if it exceeds 0.15 g, the pore structure of ZIF-8 may be affected, thereby reducing its drug loading capacity. 2+ and Ni 2+ The ratio not only improves the antibacterial effect of the material, but also enhances the stability of the material under different environmental conditions.
[0051] 3. Composite component group: Sodium alginate: The ratio of sodium alginate is 1-1.5g. As the main material of the composite component group, sodium alginate plays an important role in sustained-release materials; Sodium alginate (1-1.5g): Within this ratio range, sodium alginate can be fully compounded with ZIF-8 to form a uniform hydrogel structure, thereby improving the biocompatibility and sustained-release performance of the material. If the amount of sodium alginate is less than 1g, the composite effect is poor and the surface of ZIF-8 cannot be effectively covered; if the amount of sodium alginate exceeds 1.5g, the viscosity of the solution may be too high, affecting the dispersion and uniformity of the composite material. The optimized ratio of the composite component group can ensure the effective modification of ZIF-8 and the sustained-release performance of the drug, so that the sustained-release material exhibits excellent biocompatibility and sustained efficacy in different application environments.
[0052] 4. Loading component group: tetracycline, the ratio range of tetracycline is 0.1-0.15g. As an antibacterial drug, the reasonable loading of tetracycline in the sustained-release material can achieve the sustained release of drug efficacy; tetracycline (0.1-0.15g): within this ratio range, tetracycline can achieve efficient loading in ZIF-8 while maintaining stable sustained-release performance. If the loading amount of tetracycline is less than 0.1g, the drug concentration is insufficient and it is difficult to achieve the ideal antibacterial effect; if the loading amount of tetracycline exceeds 0.15g, it may cause the drug to be released quickly in a short time, and it is difficult to maintain the persistence of drug efficacy. Through the optimized control of the tetracycline loading amount, the present invention can not only achieve the sustained release of the drug, but also reduce the toxic reactions caused by high concentrations of drugs.
[0053] Through the reasonable proportions of the above components, the sustained-release material of the present invention shows significant advantages in antibacterial performance and drug release performance. The optimization of the component ratio enables the material to have better biocompatibility and stability in practical applications, while also improving the utilization efficiency and antibacterial effect of the drug. These optimized proportions ensure the performance of the material in a variety of application environments, making it have a wide range of application potentials in the fields of medical device coatings, wound care, and antibacterial drug release.
[0054] The present invention not only optimizes the ingredients, but also further improves the comprehensive performance of the sustained-release material by refining and regulating the physical and chemical properties.
[0055] 1. Physical and chemical properties of ZIF-8, specific surface area range: 1100-1300m 2 / g, the specific surface area of ZIF-8 within this range can provide sufficient pore structure, which is conducive to the efficient loading and sustained release of drugs. The increase in specific surface area not only increases the drug loading capacity, but also enhances the contact area of the material, so that the antibacterial performance is enhanced. Too low specific surface area may lead to insufficient drug loading capacity, while too high specific surface area may lead to excessive pore opening, affecting the sustained release effect of the drug.
[0056] Pore size range: 1.2-1.5nm. The regulation of pore size is crucial for the sustained release of drugs. The pore size of 1.2-1.5nm can effectively control the release rate of drugs. Within this range, the pores of ZIF-8 can adapt to the molecular size of tetracycline, which can not only ensure its loading capacity but also achieve sustained release effect. Too small pore size will limit the entry and release of drugs, while too large pore size may lead to rapid release of drugs in a short time.
[0057] Solubility in water: less than 0.01 g / L. The solubility of ZIF-8 in water is less than 0.01 g / L, indicating that it has good stability in water environment. This low solubility can ensure that the material will not dissolve too quickly during the sustained release process, thereby ensuring the sustained release of the drug and long-term antibacterial properties. At the same time, this water insolubility also enhances the biocompatibility of the material and reduces the side effects that may be caused by rapid dissolution.
[0058] 2.Co 2+ Physicochemical properties of modified ZIF-8
[0059] Surface cobalt ion ratio range: 10-12%, Co 2+ The proportion of Co on the ZIF-8 surface is controlled within the range of 10-12%, which can ensure 2+ The uniform distribution of cobalt ions and the formation of a stable bond with the ZIF-8 framework structure. The appropriate amount of cobalt ion modification can improve the antibacterial effect of the material and have a positive impact on its structural stability. Too low a cobalt ion content will result in a weak antibacterial effect, while too high a content may cause instability or increased toxicity of the material.
[0060] The antibacterial rate range for Escherichia coli is 85-98%, Co 2+ The modified ZIF-8 showed a high antibacterial rate of 85-98% in the Escherichia coli antibacterial experiment, showing its excellent antibacterial properties. This antibacterial effect mainly comes from the bactericidal activity of cobalt ions and the pore structure of ZIF-8. The synergistic effect of the two enhances the material's ability to destroy bacteria. The improvement in the antibacterial rate also shows the broad prospects of the present invention in antibacterial applications.
[0061] 3.Ni 2+ Physical and chemical properties of modified ZIF-8, nickel ion attachment rate range: 8-10%, Ni 2+ The attachment rate on the ZIF-8 surface ranges from 8 to 10%, and this range of nickel ion modification can further improve the antibacterial persistence and durability of the material. 2+ Reasonable attachment of nickel ions can enhance the antibacterial properties of the material without affecting the pore structure of ZIF-8, and has an inhibitory effect on a variety of microorganisms. A nickel ion content below 8% will result in insufficient antibacterial properties, while a nickel ion content exceeding 10% may induce toxic reactions.
[0062] Stability time range in solution: 24-30 hours, Ni 2+ The stability time of the modified ZIF-8 in the solution is controlled at 24-30 hours, which ensures the durability and antibacterial effect of the material in different environments. This stability can maintain the antibacterial performance for a long time and is suitable for application scenarios requiring long-term antibacterial effects.
[0063] 4. Drug loading efficiency and release performance of tetracycline, drug loading efficiency range: 70-80%: The drug loading efficiency of tetracycline in ZIF-8 ranges from 70-80%, showing the high loading capacity of ZIF-8 as a drug carrier. Within this efficiency range, tetracycline can be evenly distributed in the pores of ZIF-8 and form strong physical or chemical adsorption with ZIF-8. This efficient drug loading provides a sufficient basis for the long-term release of drugs. The cumulative release range within 6-8 hours and 37°C: 60-80%: Under a body temperature environment of 37°C, the cumulative release range of tetracycline is 60-80%, indicating that the sustained-release material can achieve a relatively ideal sustained release of drug efficacy under physiological conditions. The 6-8 hour sustained-release process can effectively avoid the instantaneous high concentration release of drugs, thereby reducing unnecessary side effects and improving the utilization efficiency of drugs.
[0064] Through the specific analysis and optimization of the above physical and chemical properties, the sustained-release material of the present invention has shown significant advantages in antibacterial performance, drug loading efficiency and release persistence, etc. The clear definition of these physical and chemical parameters not only improves the controllability and reliability of the material of the present invention, but also makes it have broad application prospects in the fields of medical treatment, antibacterial coatings, drug sustained release, etc.
[0065] The preparation method of the present invention aims to construct a material with excellent antibacterial performance and sustained-release effect through scientific and reasonable operating steps and process conditions.
[0066] S1. Synthesis of ZIF-8 framework material: ZIF-8 is the core framework component of the present invention. Each operation step and condition in the synthesis process has an important influence on the performance of the final material.
[0067] S11. Preparation of a mixed solution: 0.8-1.0 g of zinc nitrate hexahydrate and 0.4-0.6 g of 2-methylimidazole were dissolved in 80 mL of NN-dimethylformamide (DMF) with a stirring speed of 300 rpm and a stirring time of 15 minutes. The temperature was controlled at 25°C.
[0068] In this step, DMF as a solvent can provide good dissolution ability and ensure that the precursor components of ZIF-8 are fully dispersed. The stirring speed of 300rpm helps to mix the uniformity of the solution while avoiding excessive accumulation of local components or incomplete reaction. The room temperature environment of 25℃ helps to maintain the stability of the solution and prevent the components from reacting too quickly.
[0069] S12. Hydrothermal reaction: The mixed solution obtained in S11 was transferred to an autoclave, and the temperature was raised to 140° C. at a heating rate of 5° C. / min, and crystallized at this temperature for 24 hours.
[0070] The hydrothermal reaction is a key step in the formation of ZIF-8 crystals. By gradually increasing the temperature to 140°C, the stable growth of ZIF-8 crystals can be promoted. Controlling the heating rate to 5°C / min can avoid crystal defects or uneven growth caused by too fast heating, thereby improving the quality of the crystals and the structural integrity of the material.
[0071] S13. Separation and drying of solid powder: The product after the reaction was centrifuged, washed 3 times with 50 mL of DMF and methanol respectively, and then dried overnight at 80 ° C to obtain ZIF-8 skeleton powder. Centrifugal separation is used to remove unreacted residual substances and fully separate the ZIF-8 crystal powder. Washing with DMF and methanol can further remove impurities and enhance the purity of the material. The drying temperature is set to 80 ° C to ensure the integrity of the ZIF-8 crystals and avoid residual moisture. Overnight drying can completely dehydrate the material and improve the effect of subsequent modification and loading.
[0072] S2. Modification and compounding of ZIF-8: ZIF-8 was modified by Co 2+ and Ni 2+ The modification of the antibacterial properties and drug carrier function are significantly improved.
[0073] S21, Co 2+ Modification: 0.1-0.2 g of cobalt sulfate hexahydrate was dissolved in 20 mL of deionized water, and then 0.5 g of ZIF-8 framework powder was added, with a stirring speed of 300 rpm and a stirring time of 1 hour.
[0074] The addition of cobalt ions can improve the antibacterial properties of ZIF-8. 2+ Uniform adsorption on the surface of ZIF-8 and 1 hour of stirring time allow cobalt ions to fully combine on the pore surface of ZIF-8 to form a stable modification layer, enhancing the material's ability to inhibit bacteria.
[0075] S22, Ni 2+ Modification: 0.05-0.15 g of nickel chloride was dissolved in 20 mL of deionized water and added to the ZIF-8 / Co obtained in S21. 2+ The composite was stirred at a speed of 300 rpm for 1 hour.
[0076] The modification of nickel ions further enhances the antibacterial and drug carrier properties of ZIF-8. 2+ In ZIF-8 / Co 2+ Multi-layer modifications are formed on the basis of the material to enhance the stability and antibacterial durability of the material.
[0077] S23, solid separation and drying: The modified product was centrifuged, washed with deionized water three times, and dried at 60°C for 12 hours to obtain Co 2+ and Ni 2+ Modified ZIF-8.
[0078] Centrifugal separation and water washing are used to remove free cobalt and nickel ions to ensure the purity of the final product. Low-temperature drying at 60°C helps to protect the modified material structure from damage and avoid the impact of high temperature on antibacterial properties.
[0079] S3. Preparation of sodium alginate complex: The sodium alginate complex is used as a coating layer of the ZIF-8 complex, which further enhances the biocompatibility and sustained-release effect of the sustained-release material.
[0080] S31. Preparation of sodium alginate solution: at room temperature, dissolve 1.0-1.5 g of sodium alginate in 100 mL of deionized water, stirring at a speed of not less than 350 rpm until completely dissolved.
[0081] A higher stirring speed and sufficient dissolution time can ensure the uniformity of the sodium alginate solution, thereby forming a stable hydrogel matrix, providing a good coating basis for the subsequent composite process.
[0082] S32. Formation of composite materials: 0.8-1.0 g of the modified ZIF-8 was gradually added to the sodium alginate solution of S31, with a stirring speed of 300 rpm and a stirring time of 20 minutes.
[0083] By gradually adding ZIF-8 materials and making them fully contact with sodium alginate during stirring, a stable complex is formed. The coated composite material has better sustained-release performance and biocompatibility, ensuring the long-term release of the drug.
[0084] S4. Tetracycline loading and drying: The tetracycline loading step ensures the antimicrobial efficacy of the sustained-release material.
[0085] S41. Preparation of tetracycline solution: Dissolve 0.1-0.15 g of tetracycline in 30 mL of PBS solution at pH 7.4, with a stirring speed of 400 rpm and a stirring time of 15 minutes.
[0086] PBS buffer can maintain the dissolution environment of tetracycline while maintaining the activity of the drug. The stirring speed of 400rpm helps to increase the dissolution rate of tetracycline in the solution, making its molecules evenly dispersed, providing a good solution basis for subsequent loading.
[0087] S42. Impregnation and loading of tetracycline: 0.5 g of the composite material obtained in S32 was added to the tetracycline solution in S41 and stirred at room temperature for 24 hours.
[0088] The impregnation loading process allows tetracycline molecules to gradually enter the pore structure of ZIF-8, achieving efficient drug loading. Long-term stirring ensures the full combination of the drug and the carrier, enhancing the sustained-release effect.
[0089] S43, separation and freeze drying of solids: The impregnated product was centrifuged, the supernatant was discarded, washed three times, and the solid was freeze dried for 12 hours. Freeze drying technology can effectively remove moisture and maintain the structural stability and antibacterial properties of the sustained-release material. The resulting sustained-release material not only has a good antibacterial effect, but also has the ability to release drugs for a long time.
[0090] On the basis of the original preparation method, the operating conditions of the key steps were further refined to improve the structural stability and drug loading effect of the sustained-release material, including: pH adjustment in step S11.
[0091] In step S11, the pH of the mixed solution of zinc nitrate hexahydrate and 2-methylimidazole is adjusted to maintain the pH range of the solution in the range of 6.5-7.0. pH adjustment helps to improve the formation efficiency of the ZIF-8 skeleton. 2+ The complexation reaction between ZIF-8 and 2-methylimidazole is more stable, which is conducive to uniform crystal growth and thus forms a higher quality ZIF-8 framework.
[0092] Intermittent heating in step S12: During the hydrothermal reaction in step S12, the temperature was raised from 100°C to 140°C every 30 minutes and maintained at the highest temperature for 30 minutes. The intermittent heating setting helps to control the uniform growth of ZIF-8 crystals. The staged heating reduces crystal defects caused by excessive heating and helps to improve the crystallinity and purity of the crystals.
[0093] Constant temperature air drying in step S13: During the drying process in step S13, constant temperature air drying is adopted, the temperature range is controlled at 60-70°C, and the drying time is 12-16 hours. Constant temperature air drying can effectively remove residual solvents and impurities on the surface of ZIF-8 while maintaining the pore structure of the material. The drying temperature of 60-70°C can avoid the damage of high temperature to the material structure and ensure that the drying time is long enough to achieve efficient moisture removal.
[0094] The above steps also include the 2+ and Ni 2+ The modification process and drying conditions were improved to enhance the adhesion and stability of the sustained-release material.
[0095] Addition of chelating agent in steps S21 and S22: In steps S21 and S22, sodium citrate is added as a chelating agent, and the addition ratio is 0.05-0.1% of the total mass of the solution. Sodium citrate as a chelating agent helps stabilize Co 2+ and Ni 2+ The addition of chelating agents can improve the dispersibility of metal ions, prevent ion aggregation, and enhance the antibacterial properties of the material.
[0096] Vacuum drying in step S23: During the drying process in step S23, vacuum drying is used, the vacuum degree is not less than 0.08MPa, and the drying time ranges from 8 to 10 hours. Vacuum drying can prevent metal ion oxidation by reducing the oxygen content in the air, while ensuring the purity and stability of the material. Appropriate vacuum degree and drying time can ensure that the moisture in the material is fully removed and its original antibacterial properties are maintained.
[0097] Centrifugal separation in step S23: During the centrifugal separation process in step S23, the centrifugal speed is 4000-5000 rpm and the centrifugal time is 10-15 minutes. A higher centrifugal speed and an appropriate centrifugal time can effectively separate the modified ZIF-8 composite material and ensure the purity of the product. Reasonable centrifugal conditions can also reduce the loss of material particles and improve the yield of the product.
[0098] This solution also optimizes the compounding process of sodium alginate and the loading process of tetracycline, so as to further improve the sustained release effect of the material and the uniform loading of the drug;
[0099] Preparation of sodium alginate solution in step S31: In step S31, the stirring speed of the sodium alginate solution is gradually increased to 400 rpm, and the dissolution environment is maintained within a temperature range of 30-35°C. Gradually increasing the stirring speed can accelerate the dissolution process of sodium alginate, while the dissolution temperature of 30-35°C helps to improve the dissolution efficiency of sodium alginate and maintain the uniformity of the solution. Such conditions can provide better coating effects for the subsequent composite process.
[0100] Ultrasonic assisted loading in step S42: During the tetracycline impregnation loading process in step S42, ultrasonic assisted loading is used, with an ultrasonic frequency range of 20-40kHz and an ultrasonic time of 15-20 minutes. Ultrasonic assisted loading can accelerate the entry of tetracycline molecules into the pore structure of ZIF-8 through the vibration of ultrasonic waves, thereby improving the loading efficiency and uniformity of the drug. Ultrasonic treatment can also destroy aggregated drug molecules, allowing them to be better dispersed in the carrier material.
[0101] Freeze drying in step S43: In step S43, the sample is precooled to -20°C and then vacuum freeze dried for 10-12 hours. Precooling to -20°C can effectively freeze the water in the sample, while vacuum freeze drying removes the water by sublimation, thereby maintaining the structural stability and porosity characteristics of the material. Appropriate drying time ensures the stability of the drug and the sustained release effect of the material.
[0102] In order to better demonstrate the applicability and advantages of the antibacterial sustained-release material and its preparation method described in the present invention under different experimental conditions, the following is a detailed description in combination with multiple embodiments. The present invention successfully achieves the improvement of the antibacterial effect of the material, the optimization of the drug sustained-release performance and the enhancement of biocompatibility through the synthesis and modification of the ZIF-8 skeleton material, the compounding of sodium alginate and the loading of tetracycline. The specific examples will show the experimental results of the material in terms of antibacterial performance, cell activity effect, tetracycline loading and release performance, and further verify its application potential in the field of antibacterial drug carriers;
[0103] The reagents and instruments required in this embodiment are as follows:
[0104] Reagents: methanol, anhydrous ethanol, cobalt acetate, zinc nitrate hexahydrate, fluonic acid, NN-dimethylformamide (DMF), imidazole, 2-methylimidazole, lipoic acid, zinc acetate, tetracycline, sodium alginate, agar powder, glucose (monohydrate), sodium chloride, peptone, beef extract.
[0105] Instruments: electronic analytical balance (accuracy: one ten-thousandth), electric blast drying oven, heat-collecting constant temperature heating magnetic stirrer (DF-101S), UV-visible spectrophotometer (UV-1800PC), transmission electron microscope (JEM-2100F), scanning electron microscope (JSM-7800F).
[0106] Example 1: Inhibition rate of ZIF-8, Co2+ / ZIF-8, ZIF-8 / Ni2+, ZIF-8 / Ni2+ / SA on Escherichia coli
[0107] The specific experimental steps are as follows: prepare the solid culture medium: weigh 5g beef extract, 10g peptone, and 5g sodium chloride and dissolve them in 500mL distilled water, adjust the pH to 7.2 with 10% sodium hydroxide solution, and then make the solution constant to 1000mL. The resulting solution is divided into ten portions and dispensed into conical flasks, five of which are added with 2.4g shredded agar, and sterilized at 121℃ for 20min. After cooling, seal with plastic wrap, store upside down at 4℃ for later use, and record as agar solid culture medium.
[0108] Use a sterilized inoculation loop to pick up a small amount of bacteria and perform the streak method on the agar solid culture medium. After the operation, burn off the residual bacteria on the inoculation loop for next use. Invert the streaked plate and culture it in an environment at 37°C. Observe the bacterial growth every 24 hours.
[0109] The MTT (3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2-H-tetrazoliumbromide) reduction test is a method for detecting cell survival and growth. Because the mitochondria of living cells contain succinate dehydrogenase, this substance can reduce exogenous MTT to water-insoluble blue-purple crystalline formazan and deposit it in the cells, while dead cells do not have this phenomenon. Dimethyl sulfoxide (DMSO) can dissolve the formazan in the cells to form a clear solution with different shades of color. The optical density value (OD value) at 490nm can be detected by a microplate reader to indirectly determine the number of living cells in the solution, which can also reflect the bactericidal ability of different materials. The higher the OD value, the more surviving bacteria there are in the bacterial solution; the lower the OD value, the worse the bacterial growth in the bacterial solution and the fewer surviving bacteria there are.
[0110] Before conducting the MTT reduction experiment, the MTT solution must be prepared as follows: weigh 8g NaCl, 0.2g KCl, 1.44g Na2HPO4 and 0.24g KH2PO4 in a 100mL volumetric flask, add 800mL deionized water, adjust the pH value of the solution to 7.4 with HCl, and finally make the solution to 1000mL with deionized water. After that, the solution is sterilized under high temperature and high pressure and stored at 4°C, which is recorded as 0.01mol / L phosphate buffer (PBS); weigh 0.5g MTT, dissolve it in 100mL PBS, filter it with a 0.22nm filter to remove bacteria in the solution, and divide the filtered solution into small doses in centrifuge tubes, wrap it with aluminum foil and store it at -20°C away from light, which is recorded as 5mg / mL MTT reagent.
[0111] The specific operation steps of the MTT reduction experiment are as follows: aspirate the liquid culture medium, and adjust the OD value of the microplate reader to zero based on the culture medium. Then take the bacterial solution with good activity, add the liquid culture medium, and constantly adjust the ratio of the bacterial solution to the culture medium so that the value of the microplate reader falls between 0.135 and 0.15. At this time, the bacterial concentration is 108 CFU / mL. The bacterial concentrations in the following text are all configured according to this method. Take the configured ZIF-8, Co 2+ / ZIF-8, ZIF-8 / Ni 2+ 、ZIF-8 / Ni 2+ / SA, 2-methylimidazole, 1mL of niflumic acid solution were added to different test tubes, and then 250μL of experimental bacteria with a concentration of 108CFU / mL was added to the test tubes, and finally 4.75mL of liquid culture medium was added. Three parallel experimental groups were set up for each concentration. 250μL of bacterial solution and 5.75mL of culture medium were added to the test tubes, and this group was defined as the blank control group; the blank group and the experimental group were cultured in an anaerobic environment at 37°C. After culturing for 2h, 50μL of MTT reagent was added to each group, and then the test tubes were placed in an anaerobic environment at 37°C for 2h in a dark environment. The upper layer of liquid was removed from the test tube by centrifugation, leaving purple crystals, 200μL of DMSO solution was added to the test tube, and the crystals were completely dissolved by centrifugation again. The appropriate amount of solution was transferred to a 96-well plate, and the OD value was measured with an enzyme marker at 490nm. The OD values of different concentrations and different metal ions were processed and plotted to obtain the MTT experimental results.
[0112] The results of MTT reduction experiment are as follows Figure 3 As shown in the figure, the survival rates of Escherichia coli in ZIF-8, ZIF-8 / Co2+, ZIF-8 / Ni2+, ZIF-8 / Ni2+ / SA, 2-methylimidazole, and niflumic acid are shown. It can be seen from the figure that for ZIF-8, adding different metal ion modifications has different bactericidal effects. The antibacterial effect of ZIF-8 / Co2+ material is better, reaching 98%, and has a significant bactericidal effect. Comprehensive experimental results show that ZIF-8 and other MOFs materials have certain bactericidal effects on bacteria.
[0113] Example 2: Effects of sodium alginate / ZIF-8, ZIF-8, and sodium alginate on phagocyte activity
[0114] The cytotoxicity of metal-organic framework materials ZIF-8, sodium alginate, and sodium alginate / ZIF-8 was studied using MTT colorimetry. 4 Pieces / cm 2 The phagocytes were seeded in a 96-well plate at a density, and then different concentrations (0.5, 1, 2, 5, 10, 20, 50, 100, 200, 500 μg / mL) of material solutions were added. Six replicate wells were set for each concentration, and a control sample of only seeded cells without adding material was set. Then, the 96-well plate was placed in a cell culture incubator and cultured for 24 hours. After the culture was completed, 50 μL of MTT solution was added to each well and cultured for another 4 hours. After removing the culture medium, 150 μL of DMSO was added to dissolve the formazan generated by the cells. After 30 minutes, the 96-well plate was placed in an enzyme-linked immunosorbent assay to test the optical density (OD) of the solution. Finally, the cell survival rate was calculated according to the following formula: The above steps were repeated for 48 hours to obtain the survival rate of phagocytes treated with different materials.
[0115] The effects of sodium alginate / ZIF-8, sodium alginate, and ZIF-8 materials on mitochondrial activity of phagocytes were detected by MTT colorimetry. Figure 4 ), as can be seen from the figure, as the concentration of the material increases, the survival rate of the phagocytes decreases, indicating that the increase in the concentration of the material has a certain effect on the metabolism of the cell mitochondria. Sodium alginate is less toxic and has little effect on the activity of phagocytes, while ZIF-8 contains metal ions, which have certain toxicity, causing a low survival rate of phagocytes and weak biocompatibility. Directly using ZIF-8 material as a drug carrier can cause great damage to human cells. After the ZIF-8 material is modified with sodium alginate, the survival rate of the cells remains above 65% within the material concentration range of 5-100 μg / mL. Overall, the toxicity of sodium alginate / ZIF-8 materials to cells is reduced and biocompatibility is enhanced.
[0116] Example 3: Drug loading efficiency of tetracycline in ZIF-8, sodium alginate, and sodium alginate / ZIF-8
[0117] In this experiment, the tetracycline loading rate of ZIF-8, sodium alginate, and sodium alginate / ZIF-8 was determined by the standard curve method. The specific experimental steps are as follows: standard curve drawing: 0, 0.1, 0.5, 1.0, 1.5, 2.0, and 2.5 mL of tetracycline hydrochloride standard solution were added to 12 25 mL colorimetric tubes in sequence, and the results were determined after treatment according to the experimental method. The linear regression equation was obtained: A = -0.0095 + 0.0305 * C, where A is the absorbance and c is the concentration of TC (mg / L). The correlation coefficient r = 0.9997, the molar absorption coefficient (ε = 1.33 × 10 4 ); According to IUPAC regulations, the detection limit is calculated to be 0.40 mg / L. Figure 1 The results showed that the concentration of tetracycline in the range of 0.80-25 mg / L fully complies with Beer's law.
[0118] Accurately weigh 100 mg of ZIF-8 powder, dissolve it in 30 mL of 4 mmol / L tetracycline solution, mix well, add a magnetic particle, seal the beaker with a sealing film, and place it on a constant temperature magnetic stirrer for 24 hours. Then divide it into centrifuge tubes and centrifuge (10000r / min, 10min), then pour the supernatant into the centrifuge tube, wash the remaining solid with deionized water for more than 3 times, and then freeze-dry the obtained solid for 12 hours to obtain a ZIF-8-tetracycline complex. Finally, centrifuge the supernatant again, measure its absorbance, calculate the content of tetracycline in ZIF-8 according to the established standard curve, and calculate the drug loading M of ZIF-8 according to the following formula. Drug loading calculation, calculate the drug loading M of ZIF-8 according to the following formula:
[0119] M ZIF-8上清液总质量 =c ZIF-8上清液的浓度 ×V 四环素 ×M 四环素
[0120] M ZIF-8内药量 =M ZIF-8总质量 -M ZIF-8上清液的总质量 ,
[0121] Where: M ZIF-8总质量 100mg; V 四环素 30×10 -3 L; M 四环素 The drug loading calculation steps of sodium alginate solid and sodium alginate / ZIF-8 are the same as above;
[0122] Drug loading curve Figure 5 It can be seen that within 0-20h, the drug loading speed is fast. As time goes on, the drug loading speed gradually tends to be flat, and the adsorption rate of drugs by sodium alginate / ZIF-8, sodium alginate, and ZIF-8 materials decreases. It can be inferred that the drug loading process of the material is free diffusion, and the greater the concentration difference, the faster the adsorption rate. After 24 hours, the drug loading is close to saturation, and the drug loading rates of the three materials are all low. Under the same conditions, sodium alginate / ZIF-8 has a higher drug loading rate than sodium alginate or ZIF-8 materials, has excellent drug loading capacity, and is more suitable for use as a drug carrier.
[0123] Example 4: Determination of in vitro tetracycline release performance of ZIF-8, sodium alginate, and sodium alginate / ZIF-8 composite materials
[0124] Weigh a certain mass of tetracycline-loaded ZIF-8 solid, put it into a dialysis bag, add 10mL of PBS solution (pH=5.29), tie the dialysis bag with fine cotton thread, put it into a conical flask, add 30mL of PBS solution (pH=5.29) into the conical flask, put it into a water bath constant temperature oscillator (oscillation speed is 100r / min), start timing after oscillation for 5min, sample at intervals of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12h, take 5mL each time, and add an equal amount of fresh PBS solution (pH=5.29). Finally, use an ultraviolet spectrophotometer to measure the absorbance of the drug, calculate the cumulative concentration and cumulative release rate according to the standard curve, make a relationship curve between cumulative release rate and time, and investigate the in vitro release performance of ZIF-8 after drug loading. The in vitro release tetracycline performance determination method of sodium alginate solid and sodium alginate / ZIF-8 is the same as above.
[0125] refer to Figure 2 From the scanning electron microscope image of the sample, it can be seen that the crystal particles were successfully synthesized and there was agglomeration.
[0126] Example 5: Determination of the release performance of sodium alginate / ZIF-8, ZIF-8, and sodium alginate loaded with the antibacterial drug tetracycline
[0127] refer to Figure 6 , it can be seen from the release curve that the release rate changes with time. In the first 3 hours, the release curve is steep and the drug release rate is fast. This is caused by the diffusion of tetracycline adsorbed on the surface of sodium alginate / ZIF-8, sodium alginate, and ZIF-8 materials into the release medium; within 3-7 hours, the release curve becomes more and more gentle, and the drug release amount is the largest, which means that with the extension of time, the tetracycline in the pore size of the material is slowly released, showing an obvious sustained release effect; within 7-12 hours, the release curve tends to be stable, and the release rate is almost unchanged. Under the same conditions, the tetracycline release rate of ZIF-8 is significantly higher than that of the mixture of sodium alginate / ZIF-8 and sodium alginate. The release rate of the mixture of sodium alginate / ZIF-8 is relatively slow. ZIF-8 crystals are acid-instable, and the structure collapses under acidic conditions. The stronger the acidity, the faster the structural collapse. After ZIF-8 is surface modified with sodium alginate, its structure becomes more stable and less susceptible to destruction. The antibacterial drug tetracycline is encapsulated in such a framework structure, and its release rate is lower.
[0128] Example 6: Determination of the release performance of tetracycline in a mixture of sodium alginate / ZIF-8 at different pH values
[0129] refer to Figure 7, in two different environments, the release curves of the drug tetracycline have similar trends: in the early stage of drug release, the material release rate is faster and the release amount is larger; in the subsequent release process, the release rate and release amount slow down. Comparing the dissolution and release under acidic and weak alkaline conditions, it can be seen that the release rate in the acidic environment is significantly higher than that in the neutral environment, and the tetracycline release rate is higher. This is because ZIF-8 is an acid-unstable substance. After ZIF-8 is surface-modified with sodium alginate, its structure will collapse to a certain extent under acidic conditions (stomach environment), which accelerates the dissolution of the drug adsorbed inside. In a weak alkaline environment (intestinal environment), the structure is relatively stable, and the drug dissolution mainly relies on diffusion migration, with a slow release rate and a low release rate. After sodium alginate / ZIF-8 loads the drug, the pH response release of the drug tetracycline is achieved through the difference in stability in different pH environments, that is, more drug molecules are released in the gastric environment, and a small amount of tetracycline is released in the intestinal environment (Ph7.4), which has a good controlled release effect.
[0130] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A sustained-release material with antibacterial properties, characterized in that: The sustained-release material consists of the following components: Core component group: ZIF-8; Modified component group: Co2+, Ni 2 +; composite component group: sodium alginate; loading component group: tetracycline; the ZIF-8 is composed of Zn2+ (zinc nitrate hexahydrate) and 2-methylimidazole.
2. The sustained-release material with antibacterial properties according to claim 1, characterized in that: The ratio range of each component is: Core component group: ZIF-8, Zn2+ (zinc nitrate hexahydrate) is 0.8-1.0g; 2-methylimidazole is 0.4-0.6g; Modified component group: Co2+ is 0.1-0.2g; Ni 2 + is 0.05-0.15g; complex component group: sodium alginate is 1-1.5g; loading component group: tetracycline is 0.1-0.15g.
3. The sustained-release material with antibacterial properties according to claim 2, characterized in that: The specific ratio range of each component is: Core component group: In ZIF-8, the ratio of Zn2+ is 0.85-0.95g; the ratio of 2-methylimidazole is 0.45-0.55g; Modified component group: The ratio of Co2+ is 0.12-0.18g; Ni 2 + ratio range is 0.08-0.12g; composite component group: sodium alginate ratio range is 1.1-1.3g; loading component group: tetracycline ratio range is 0.11-0.14g.
4. The sustained-release material with antibacterial properties according to claim 1, characterized in that: The specific surface area of ZIF-8 is in the range of 1100-1300 m 2 / g, its pore size range is 1.2-1.5nm, and its solubility in water is less than 0.01g / L; the surface cobalt ion ratio of the Co2+ modified ZIF-8 is in the range of 10-12%, and the antibacterial rate against Escherichia coli is in the range of 85-98%; the Ni 2 The nickel ion attachment rate of the modified ZIF-8 is in the range of 8-10%, and the stability time in the solution is in the range of 24-30 hours; the drug loading efficiency of the tetracycline in ZIF-8 is in the range of 70-80%, and the cumulative release amount thereof within 6-8 hours at 37°C is in the range of 60-80%.
5. A method for preparing a sustained-release material with antibacterial properties, applied to the sustained-release material with antibacterial properties as claimed in any one of claims 1 to 4, characterized in that: The following steps are involved: S1. Synthesis of ZIF-8 framework material: S11, preparation of mixed solution: 0.8-1.0g of zinc nitrate hexahydrate and 0.4-0.6g of 2-methylimidazole were dissolved in 80mL of NN-dimethylformamide (DMF), the stirring speed was 300rpm, the stirring time was 15 minutes, and the temperature was controlled at 25°C; S12, hydrothermal reaction: the mixed solution obtained in S11 was transferred to an autoclave, the temperature was increased to 140°C at a heating rate of 5°C / min, and crystallized at this temperature for 24 hours; S13, separation and drying of solid powder: the product after the reaction was completed was centrifuged, washed 3 times with 50mL of DMF and methanol respectively, and then dried at 80°C overnight to obtain ZIF-8 skeleton powder; S2. Modification and compounding of ZIF-8: S21, Co2+ modification: 0.1-0.2 g of cobalt sulfate hexahydrate was dissolved in 20 mL of deionized water, and then 0.5 g of ZIF-8 skeleton powder was added, and the stirring speed was 300 rpm for 1 hour to complete the modification of surface cobalt ions; S22, Ni 2 + modification: 0.05-0.15g of nickel chloride was dissolved in 20mL of deionized water, and the ZIF-8 / Co2+ complex obtained in S21 was added, with a stirring speed of 300rpm and a stirring time of 1 hour to complete the modification of nickel ions; S23, solid separation and drying: the modified product was centrifuged, washed with deionized water for 3 times, and dried at 60°C for 12 hours to obtain Co2+ and Ni 2 + modified ZIF-8; S3. Preparation of sodium alginate complex: S31, preparation of sodium alginate solution: at room temperature, dissolve 1.0-1.5 g of sodium alginate in 100 mL of deionized water, stirring at a speed of not less than 350 rpm, stirring until completely dissolved to form a sodium alginate solution; S32, formation of composite material: gradually add 0.8-1.0 g of modified ZIF-8 to the sodium alginate solution of S31, stirring at a speed of 300 rpm, stirring for 20 minutes, to form a sodium alginate / ZIF-8 composite; S4. Loading and drying of tetracycline: S41, preparation of tetracycline solution: dissolve 0.1-0.15 g of tetracycline in 30 mL of PBS solution with a pH of 7.4, with a stirring speed of 400 rpm and a stirring time of 15 minutes; S42, impregnation and loading of tetracycline: add 0.5 g of the composite material obtained in S32 to the tetracycline solution of S41, and stir at room temperature for 24 hours to fully load the tetracycline; S43, separation and freeze-drying of the solid: centrifuge the impregnated product, discard the supernatant, wash 3 times, and freeze-dry the solid for 12 hours to obtain the final sustained-release material.
6. The method for preparing a sustained-release material with antibacterial properties according to claim 5, characterized in that: In step S11, the mixed solution of zinc nitrate hexahydrate and 2-methylimidazole is further included to be pH-adjusted to maintain the pH value in the range of 6.5-7.0; in the hydrothermal reaction process of step S12, an intermittent heating method is adopted, i.e., the temperature is raised from 100°C to 140°C every 30 minutes and maintained at the highest temperature for 30 minutes; in the drying process of step S13, constant temperature air drying is adopted, the temperature range is controlled at 60-70°C, and the drying time is 12-16 hours.
7. The method for preparing a sustained-release material with antibacterial properties according to claim 5, characterized in that: The Co2+ and Ni 2 + The modification process also includes adding sodium citrate as a chelating agent, with the addition ratio being 0.05-0.1% of the total mass of the solution; In the drying process of step S23, vacuum drying is adopted, the vacuum degree is not less than 0.08 MPa, and the drying time ranges from 8 to 10 hours; During the centrifugal separation process in step S23, the centrifugal speed is 4000-5000 rpm, and the centrifugal time is 10-15 minutes.
8. The method for preparing a sustained-release material with antibacterial properties according to claim 5, characterized in that: In the sodium alginate solution preparation process of step S31, the stirring speed of the solution is gradually increased to 400 rpm, and the dissolution environment is maintained within a temperature range of 30-35° C.; In the tetracycline impregnation loading process of step S42, ultrasound-assisted loading is also used, the ultrasound frequency range is 20-40kHz, and the ultrasound time is 15-20 minutes; During the freeze-drying process of step S43, the sample is precooled to -20°C and then subjected to vacuum freeze drying for 10-12 hours.